STUDI MENGENAI PERILAKU PENYESUAIAN DIRI UNTUK MENINGKATKAN KINERJA PENJUALAN (Studi terhadap Tenaga Penjual pada lndustri Asuransi di Kota Semarang) - Sulistiyawati, Erika; Soesanto, Harry (Master of Management Diponegoro University, 2003)
In insurance industry, salesperson plays such an important role in promoting the product of insurance. In order to understand that important role. it is necessary to understand the characteristics or abilities required by the sales person to improve the soles performance. Even though a salesperson may have a complement qf adaptive psychological traits, a lack of communication skill, indicated by the less ability of listening will impede success in sales Interactions. Therefore, this research proposes a problem whether listening ability could mediate the relationship between psychological adaptiveness in selling (self monitoring and empathy) and sales performance. This research aims to analyze the effect of listening ability as mediator in relationship between psychological adaptiveness in selling (self-monitoring and empathy) and sales performance. A model has been developed and 5 hypotheses haw been proposed lo meet the research problemthrough SEM analysis. The object of this research Is the sales person qf insurance company in Semarang city. in which the samples are determined by applying double sampling method, a combination ofpurposive and quota sampling method. The sample size 100 insurance sales person and the dala are collected by distributing questionnaires. The result of this research proved that all hypotheses could be accepted, meaning that self- monitoring and empathy have positive effect on listening ability and sales performance. also listening ability has positive effect on sales performance, and able to be explained that self-monitoring and empathy have direct effect on sales performance and might have indirect one, through listening ability as mediator.